Executive functions processed in the frontal and lateral temporal cortices: intracerebral study - Bocková, M; Chládek, J; Jurák, P; Halámek, J; Rektor, I (Clinical neurophysiology, 2007)
OBJECTIVE: The study was designed to investigate the neurocognitive network in the frontal and lateral temporal cortices that is activated by the complex cognitive visuomotor tasks of letter writing. METHODS: Eight epilepsy surgery candidates with implanted intracerebral depth electrodes performed two tasks involving the writing of single letters. The first task consisted of copying letters. In the second task, the patients were requested to write any other letter. The cognitive load of the second task was increased mainly by larger involvement of the executive functions. The task-related ERD/ERS of the alpha, beta and gamma rhythms was studied. RESULTS: The alpha and beta ERD as the activational correlate of writing of single letters was found in the sensorimotor cortex, anterior cingulate, premotor, parietal cortices, SMA and the temporal pole. The alpha and beta ERD linked to the increased cognitive load was present moreover in the dorsolateral and ventrolateral prefrontal cortex, orbitofrontal cortex and surprisingly also the temporal neocortex. Gamma ERS was detected mostly in the left motor cortex. CONCLUSIONS: Particularly the temporal neocortex was activated by the increased cognitive load. SIGNIFICANCE: The lateral temporal cortex together with frontal areas forms a cognitive network processing executive functions.
Keywords: Temporal Lobe; dominance mozková; psaní; Volition; Electroencephalography; Dominance, Cerebral; Neocortex; vůle; pohyb; Cognition; Neuropsychological Tests; Psychomotor Performance; mladiství; Hand; Brain Mapping; Middle Aged; mužské pohlaví; elektroencefalografie; Adult; ruka; psychomotorický výkon; Motor Skills; Mental Processes; motorické dovednosti; kognice; Neural Pathways; ženské pohlaví; Nerve Net; neuropsychologické testy; Humans; mapování mozku; duševní procesy; nervová síť; Frontal Lobe; Writing; Movement; lidé středního věku; nervové dráhy; neokortex; dospělí; Female; čelní lalok; spánkový lalok; Adolescent; lidé; Male